Perspectivas do aluno de uma escola pública em relação ao trabalho com os exercícios de língua inglesa propostos no Caderno do Aluno da Secretaria da Educação do Estado de São Paulo - Junqueira, Priscilla (2012)
This research is inserted in the Applied Linguistic area and intends to investigate the perspectives of the student of one public school with regard to work with proposed exercises of English language in the Student Book from the São Paulo State Education Secretariat. The sorts of exercises covered in this study are centered in grammar, which is included in language conception, and in team work. The educational context comprised is based on the São Paulo State Modern Foreign Language Curriculum, English, (SÃO PAULO, 2010), with the addition of the Student Book (SÃO PAULO, 2009a) and the Teacher Book (SÃO PAULO, 2009b). The theoretical axis is mainly based in Vigotski (1934/1991; 1934/2008) and his Social- Historical-Cultural vision. It is complemented with Koch (2003), Travaglia (1995/2005), Larsen-Freeman (2003) and Celce-Murcia (2008) for language and grammar concerns and Magalhães (2009) for team work concern. Methodologically, this research fits in a case study (STAKE, 1995; YIN, 2001) of interpretative qualitative type that uses a questionnaire (NUNAN, 1992) and an interview (RUBIN & RUBIN, 2005) as data gathering instruments. I identified ten different perspectives of students about English learning in the context of this research. The analysis of the results showed that there are some established principles in the Curriculum and in the Teacher Book which permeate the Student Book, as seen in the identified perspectives of students of English learning based on grammar, the team work positive consideration, and their collaborative role for colleagues learning. In other hand, some other perspectives showed that there are divergences between the orientation inside the Curriculum and Teacher Book and the manner how the exercises are presented in the Student Book and worked in classroom, such as the lack of activities of speaking and listening or that is only possible to learn the idiom by means of training and repetitions, as perceived by the students